Consumer and commercial law - Tilson, Judith (Law Express, 2011)
This title is designed to help you to relate all the reading and study throughout your course specifically to exam and assignment situations. Understand quickly what is required, organise your revision, and learn the keypoints with ease, to get the grades you need. Tested with examiners and students.